Ficus deltoidea promotes bone formation in streptozotocin-induced diabetic rats - Samsulrizal, Nurdiana; Goh, Yong Meng; Ahmad, Hafandi; Md Dom, Sulaiman; Azmi, Nur Syimal'ain; Mohamad Zin, Noor Syaffinaz Noo; Ebrahimi, Mahdi (Taylor and Francis, 2021)
Context: Diabetes mellitus increases the risk of bone diseases including osteoporosis and osteoarthritis. We have previously demonstrated that Ficus deltoidea Jack (Moraceae) is capable of reducing hyperglycaemia. However, whether F. deltoidea could protect against diabetic osteoporosis remains to be determined. Objective: The study examines the effect of F. deltoidea on bone histomorphometric parameters, oxidative stress, and turnover markers in diabetic rats. Materials and methods: Streptozotocin (STZ)-induced diabetic Sprague-Dawley rats (n = 6 animals per group) received one of the following treatments via gavage for 8 weeks: saline (diabetic control), metformin (1000 mg/kg bwt), and methanol leaves extract of F. deltoidea (1000 mg/kg bwt). A group of healthy rats served as normal control. The femoral bones were excised and scanned ex vivo using micro-computed tomography (micro-CT) for histomorphometric analysis. The serum levels of insulin, oxidative stress, and bone turnover markers were determined by ELISA assays. Results: Treatment of diabetic rats with F. deltoidea could significantly increase bone mineral density (BMD) (from 526.98 ± 11.87 to 637.74 ± 3.90). Higher levels of insulin (2.41 ± 0.08 vs. 1.58 ± 0.16), osteocalcin (155.66 ± 4.11 vs. 14.35 ± 0.97), and total bone n-3 PUFA (2.34 ± 0.47 vs. 1.44 ± 0.18) in parallel with the presence of chondrocyte hypertrophy were also observed following F. deltoidea treatment compared to diabetic control. Conclusions: F. deltoidea could prevent diabetic osteoporosis by enhancing osteogenesis and inhibiting bone oxidative stress. These findings support the potential use of F. deltoidea for osteoporosis therapy in diabetes.